USE OF ARTIFICIAL INTELLIGENCE IN THE CITY MANAGEMENT SYSTEM: INTERNATIONAL EXPERIENCES - Ilkhom Tursunbayevich Ismailov (Galaxy International Interdisciplinary Research Journal, 2022)
One of the solutions for creating an effective urban infrastructure management system, which is widely used in foreign cities at the moment, is the concept of "Smart City", in which artificial intelligence and information and communication technologies play a key role.